Modifikasi Skema Teknik Tanam Padi dan Bajak Sawah Berbasis Square Transposition 64-bit - Nadya Glorya Najoan; Magdalena Ariance Irene Pakereng (Maranatha University Press, 2021)
Cryptography is a study discussing mathematic technics that related to information security aspects such as secrecy, data integrity, and authenticity. Cryptography is also a method to secure data or information in the form of a password that makes it hard to understand the meaning. This research discusses how to modify a scheme while looking for random points using different pickup points and income points. While looking for the random point in the modified scheme research using the rice planting and field plow techniques, it has three testing processes which were runtest, monobit, and blockbit tests. This research used square transpositions 64-bit with the size 8x8 and it got a high result with p-value 7.32395E-10, p-value monobit 1.00000000 and p-value blockbit 1 that showed non-random result with the smallest p-value was 0.011662392 with p-value monobit 1.00000000 and the p-value blockbit 0.99990476 that made thisresearch got a random result.